Repair activities of 8-oxoguanine DNA glycosylase from Archaeoglobus fulgidus, a hyperthermophilic archaeon - Chung, JH; Suh, MJ; Park, YI; Tainer, JA; Han, YS (ELSEVIER SCIENCE BV, 2001)
Oxidative DNA damage is caused by reactive oxygen species formed in cells as by products of aerobic metabolism or of oxidative stress. The 8-oxoguanine (8-oxoG) DNA glycosylase from Archaeoglobus fulgidus (Afogg), which excises an oxidatively-damaged form of guanine, was overproduced in Escherichia coli, purified and characterized. A. fulgidus is a sulfate-reducing archaeon, which grows at between 60 and 95 degreesC, with an optimum growth at 83 degreesC. The Afogg enzyme has both DNA glycosylase and apurinic/apyrimidinic (AP) lyase activities, with the latter proceeding through a Schiff base intermediate. As expected for a protein from a hyperthermophilic organism, the enzyme activity is optimal near pH 8.5 and 60 degreesC, denaturing at 80 degreesC, and is thermally stable at high levels of salt (500 mM). The Afogg protein efficiently cleaves oligomers containing 8-oxoG:C and 8-oxoG:G base pairs, and is less effective on oligomers containing 8-oxoG:T and 8-oxoG:A mispairs. While the catalytic action mechanism of Afogg protein is likely similar to the human Ogg1 (hOgg1), the DNA recognition mechanism and the basis for 8-oxoG substrate specificity of Afogg differ from that of hOgg. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: ESCHERICHIA-COLI; STRUCTURAL BASIS; FPG PROTEIN; OGG1 GENE; CLONING; DAMAGE; ARCHAEBACTERIA; RECOGNITION; EXPRESSION; SEQUENCE